gagCEST imaging at 3 T MRI in patients with articular cartilage lesions of the knee and intraoperative validation - Söllner, Stefan; Welsch, G. H.; Gelse, Kolja; Goldmann, A.; Kleyer, Arnd; Schett, Georg; Pachowsky, Milena (Osteoarthritis and Cartilage, 2021)
Objective: The aim of this study was to compare glycosaminoglycan chemical exchange saturation transfer (gagCEST) of knee cartilage with intraoperative results for the assessment of early osteoarthritis (OA) and to define gagCEST values for the differentiation between healthy and degenerated cartilage. Design: Twenty-one patients with cartilage lesions or moderate OA were examined using 3 T Magnetic Resonance Imaging (MRI). In this prospective study, regions of interest (ROIs) were examined by a sagittal gagCEST analysis and a morphological high-resolution three-dimensional, fat-saturated proton-density space sequence. Cartilage lesions were identified arthroscopically, graded by the International Cartilage Repair Society (ICRS) score in 42 defined ROIs per patient and consecutively compared with mean gagCEST values using analysis of variance and Spearman's rank correlation test. Receiver operating characteristics (ROC) curves were applied to identify gagCEST threshold values to differentiate between the ICRS grades. Results: A total of 882 ROIs were examined and graduated in ICRS score 0 (67.3%), 1 (25.2%), 2 (6.2%) and the merged ICRS 3 and 4 (1.0%). gagCEST values decreased with increasing grade of cartilage damage with a negative correlation between gagCEST values and ICRS scores. A gagCEST value threshold of 3.55% was identified to differentiate between ICRS score 0 (normal) and all other grades. Conclusions: gagCEST reflects the content of glycosaminoglycan and might provide a diagnostic tool for the detection of early knee-joint cartilage damage and for the non-invasive subtle differentiation between ICRS grades by MRI even at early stages in clinical practice.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Cartilage; Chemical exchange saturation transfer; MRI; Osteoarthritis